Preparation method of high-conductivity copper-nickel alloy-graphite interlayer composite material
The copper-nickel alloy-graphite interlayer composite material was prepared by mixing method, and the interface quality of the graphene-copper-based composite material was improved by using copper chloride and nickel chloride intercalation agent, solving the problem of weak interface bonding and electron scattering, and achieving a breakthrough in high conductivity.
Patent Information
- Application Number
- CN202410080386.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-19
- Publication Date
- 2025-07-22
AI Technical Summary
The graphene-copper-based composite materials with high conductivity are difficult to achieve high conductivity, mainly due to the non-wetting between graphene and the copper matrix, the interface bond is weak, the interface straightness is poor, the electron scattering is severe, and the preparation process is complicated and there are many impurities, making it difficult to obtain high conductivity.
The composite intercalation reaction was carried out by mixing method, and copper chloride and nickel chloride were mixed with graphite powder as intercalation agent, and vacuum sealing, annealing reduction and hot pressing sintering to prepare copper-nickel alloy-graphite interlayer composite material to improve interface quality.
It significantly improves the conductivity of the composite material, achieves ultra-high conductivity, and simplifies the preparation process, with the conductivity reaching 106.1% IACS, close to the international annealing copper standard.
Smart Images

Figure CN120350264A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a technology for preparing graphite intercalation compounds, specifically a method for preparing a high-conductivity copper-nickel alloy-graphite interlayer composite material with a conductivity reaching 106.1% IACS. Background Art
[0002] Graphene has excellent electrical properties and can be used as an ideal reinforcement for achieving ultra-high conductivity in copper-based composites. However, due to the poor wettability between graphene and the copper matrix, the interfacial bonding of the composite material is weak and the flatness of the interface is poor. The low-quality composite interface leads to electron scattering, which limits the further breakthrough of the conductivity of the graphene / copper composite material. Taking the copper-graphite interlayer composite material as an example, the intercalating agent (mainly copper chloride) enters the graphite interlayer through reaction to generate a copper chloride-graphite intercalation compound. After annealing and reduction, the graphite in the copper-graphite interlayer composite material still maintains parallel arrangement. High-quality graphene can be further obtained by physical or chemical methods. At the same time, the interaction between the intercalated copper atoms and the carbon layer is an effective method for preparing graphene-metal composite materials. However, at present, graphite intercalation compounds are prepared using a single chloride, and the reaction products cannot achieve high conductivity. Therefore, it is of great significance to establish a new method for regulating the intercalation and composite interface structure to synthesize high-conductivity metal-graphite interlayer composite materials. Summary of the Invention
[0003] Aiming at the defects that the weak interface bonding between copper and carbon in the prior art reduces the interfacial strength in the bulk composite material and the low-quality composite interface causes electron scattering, which damages the conductivity, and the deficiencies that the reaction conditions of the existing preparation technology are relatively harsh, there are many impurities, it is difficult to obtain low-order products or pure products, and it is difficult to achieve ultra-high conductivity as a whole, the present invention provides a method for preparing a high-conductivity copper-nickel alloy-graphite interlayer composite material. The composite intercalation reaction is carried out by using a mixing method to generate a composite chloride-graphite intercalation compound, and the copper-nickel alloy-graphite interlayer composite material with a flat and uniform interface is prepared through annealing reduction and hot press sintering. It can effectively improve the problems such as poor interface quality in the graphene-copper-based composite material, which leads to electron scattering, significantly improves the conductivity of the composite material, has the characteristics of ultra-high conductivity and is easy to produce and prepare.
[0004] The present invention is realized through the following technical solutions:
[0005] The present invention relates to a method for preparing a high-conductivity copper-nickel alloy-graphite interlayer composite material. The dried graphite powder is mixed evenly with a mixture of copper chloride and nickel chloride as the intercalating agent, and after vacuum sealing treatment, it is heated to carry out a composite intercalation reaction to prepare a composite chloride-graphite intercalation compound. After further annealing reduction in a hydrogen-argon mixed gas atmosphere to obtain a copper / nickel-graphite composite powder, the copper-nickel alloy-graphite interlayer composite material is obtained through hot press sintering.
[0006] The drying treatment preferably involves heating at 100 - 120°C for 1 - 2 h to remove water vapor from the powder.
[0007] The graphite powder can be selected from one or more of expanded graphite, high-purity flake graphite, and nano-graphite powder, and is preferably expanded graphite with a particle size of 5 - 10 μm.
[0008] The components of the intercalating agent satisfy a mass ratio of C:CuCl₂:NiCl = 1:(1.5 - 2.5):(0.05 - 0.1).
[0009] The vacuum melting and sealing treatment means: placing a quartz tube with a diameter of 5 - 6 mm containing the mixed powder into an argon environment, evacuating to 10 Pa and sealing.
[0010] The composite intercalation reaction preferably occurs at 450 - 550°C for 5 - 7 days.
[0011] The composite chloride-graphite intercalation compound is preferably washed and dried before annealing and reduction. Specifically: washed with deionized water to remove residual chlorides, centrifuged at 3000 - 5000 r / min for 3 - 10 min, and vacuum dried at 70 - 80°C for 12 - 24 h after filtration.
[0012] The annealing and reduction means: placing the washed and dried composite intercalation compound powder in a crucible and putting it into a tube furnace, introducing a mixed gas of 20% hydrogen and argon, with a temperature of 400 - 500°C, and after holding for 1 - 2 h, opening the tube furnace and quickly cooling to room temperature to obtain the copper / nickel-graphite composite powder.
[0013] The hot pressing and sintering means: under argon protection in a rapid sintering furnace, using a graphite mold with a diameter of 30 - 40 mm for hot pressing and sintering, with a sintering temperature of 700 - 1000°C, a pressure of 10 - 200 MPa, and a holding time of 10 - 30 min.
[0014] The present invention relates to a composite chloride-graphite intercalation compound prepared by the above method. Specifically, copper / nickel composite chloride is inserted into the graphite layers through a composite intercalation reaction, and after reduction, chloride ions are removed to obtain a copper / nickel-graphite composite powder; the internal structure of the bulk material obtained by hot pressing and sintering is a layered configuration with copper / nickel-graphite binding slightly modified by Ni at the interface.
[0015] The present invention relates to the application of the above copper-nickel alloy-graphite interlayer composite material, which is used to prepare a conductor with a conductivity reaching 106.1% IACS. Technical effects
[0016] The present invention obtains an alloy-graphite interlayer composite material by performing a composite intercalation reaction on graphite and a composite chloride in a certain ratio, and removing chloride ions by annealing reduction in a hydrogen-argon atmosphere. Compared with the prior art, the present invention effectively improves the interface quality in the graphene-copper matrix composite material through interface modification with trace heterogeneous elements. There is a high lattice matching degree between the graphene layer and the alloy, achieving a flat composite interface at the atomic scale, and at the same time avoiding damage to the electrical conductivity, realizing high electrical conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 FIG. is a process flow chart for the preparation of a copper-nickel alloy-graphite interlayer composite material;
[0018] Figure 2 FIG. is a scanning electron microscope image of the copper-nickel alloy-graphite interlayer composite powder prepared in Example 3. DETAILED DESCRIPTION OF THE EMBODIMENTS
[0019] Table 1 shows the process parameters and material properties in the following examples Example 1
[0020] This example includes the following steps:
[0021] Step 1) Dry 1 g of expanded graphite, 1.5 g of anhydrous copper chloride, and 0.1 g of anhydrous nickel chloride (2.8 wt%) powder at 120°C for 2 h. After mixing evenly, place them in a quartz tube, evacuate to 10 Pa and seal;
[0022] Step 2) Place the sealed quartz tube in an electric heating furnace, heat it to 520°C at a rate of 10°C / min, and carry out a composite intercalation reaction for 7 days;
[0023] Step 3) Wash the prepared composite chloride-graphite intercalation compound powder with deionized water. After centrifugation and filtration, dry it in vacuo at 80°C for 12 h;
[0024] Step 4) Place the washed and dried powder in a crucible and put it into a tube furnace. Pass a mixed gas of 20% hydrogen and argon, heat it to 400°C at a rate of 10°C / min, and keep it warm for 2 h for annealing reduction to obtain a copper / nickel-graphite composite powder;
[0025] Step 5) Put the composite powder into a rapid sintering furnace and carry out hot press sintering at 900°C, 50 MPa, and in an argon atmosphere to obtain a composite block.
[0026] The thickness of the composite block prepared in step 6) is less than 1 mm, and the conductivity is measured at room temperature using a four-probe van der Pauw measurement device. The device consists of a nanovoltmeter and a constant current source. Four probes are placed around the sample. In the first measurement, current is passed through the first and second probes, and the voltage is measured between the third and fourth probes. In the second measurement, current is passed through the second and third probes, and the voltage is measured between the fourth and first probes. Finally, the conductivity of the copper-nickel alloy-graphite interlayer composite block is calculated to be 54.1×10 6 S / m, 93.2% IACS, which is close to the International Annealed Copper Standard. This shows that the copper-nickel alloy-graphite interlayer composite block prepared in this example meets the usage requirements. Example 2
[0027] This example includes the following steps:
[0028] Step 1) 1 g of expanded graphite, 2.5 g of anhydrous copper chloride, and 0.05 g of anhydrous nickel chloride (1.4 wt%) powder are dried at 120 °C for 2 h, mixed evenly, placed in a quartz tube, evacuated to 10 Pa, and sealed;
[0029] Step 2) The sealed quartz tube is placed in an electric heating furnace and heated to 520 °C at a rate of 10 °C / min for a 7-day composite intercalation reaction;
[0030] Step 3) The prepared composite chloride-graphite intercalation compound powder is washed with deionized water, centrifuged, filtered, and then vacuum dried at 80 °C for 12 h;
[0031] Step 4) The washed and dried powder is placed in a crucible and put into a tube furnace. A mixed gas of 20% hydrogen and argon is introduced, and the temperature is raised to 400 °C at a rate of 10 °C / min and held for 2 h for annealing reduction to obtain copper / nickel-graphite composite powder;
[0032] Step 5) The composite powder is put into a rapid sintering furnace and hot press sintered at 900 °C, 50 MPa, and in an argon atmosphere to obtain a composite block.
[0033] Step 6) The thickness of the composite block prepared is less than 1 mm, and the conductivity is measured at room temperature using a four-probe van der Pauw measurement device. The device consists of a nanovoltmeter and a constant current source. The specific measurement method is the same as that in step 6 of Example 1. Finally, the conductivity of the copper-nickel alloy-graphite interlayer composite block is calculated to be 56.6×10 6 S / m, 97.6% IACS, which is close to the International Annealed Copper Standard. This shows that the copper-nickel alloy-graphite interlayer composite block prepared in this example meets the usage requirements. Example 3
[0034] This example includes the following steps:
[0035] Step 1) Dry 1 g of expanded graphite, 2.5 g of anhydrous copper chloride, and 0.1 g of anhydrous nickel chloride (2.8 wt%) powder at 120 °C for 2 h. After mixing evenly, place them in a quartz tube, evacuate to 10 Pa and seal.
[0036] Step 2) Place the sealed quartz tube in an electric heating furnace and heat it to 520 °C at a rate of 10 °C / min for a 7-day composite intercalation reaction.
[0037] Step 3) Wash the prepared composite chloride-graphite intercalation compound powder with deionized water. After centrifugation and filtration, dry it in vacuo at 80 °C for 12 h.
[0038] Step 4) Place the washed and dried powder in a crucible and put it into a tube furnace. Introduce a mixed gas of 20% hydrogen and argon, heat it to 400 °C at a rate of 10 °C / min, and hold for 2 h for annealing reduction to obtain copper / nickel-graphite composite powder.
[0039] Step 5) Put the composite powder into a rapid sintering furnace and perform hot pressing sintering at 900 °C, 50 MPa, and in an argon atmosphere to obtain a composite block.
[0040] Step 6) The thickness of the prepared composite block is less than 1 mm. Use a four-point probe conductivity measurement device to measure the conductivity at room temperature. This device consists of a nanovoltmeter and a constant current source. The specific measurement method is the same as that in Step 6 of Example 1. Finally, the conductivity of the copper-nickel alloy-graphite interlayer composite block is calculated to be 61.5×10 6 S / m, 106.1% IACS, exceeding the international annealed copper standard. This shows that the copper-nickel alloy-graphite interlayer composite block prepared in this example meets the usage requirements.
[0041] As Figure 2 shown, it can be seen from the scanning electron microscope pictures that the copper / nickel-graphite composite powder still maintains a good layered structure, can form a relatively flat interface, and due to the modification of a certain content of Ni, while ensuring better interfacial bonding quality, the conductivity can be improved. Example 4
[0042] This example includes the following steps:
[0043] Step 1) Dry 1 g of expanded graphite, 2.5 g of anhydrous copper chloride, and 0.1 g of anhydrous nickel chloride (2.8 wt%) powder at 120 °C for 2 h. After mixing evenly, place them in a quartz tube, evacuate to 10 Pa and seal.
[0044] Step 2) Place the sealed quartz tube in an electric heating furnace and heat it to 450 °C at a rate of 10 °C / min for a 7-day composite intercalation reaction.
[0045] Step 3) Wash the prepared composite chloride-graphite intercalation compound powder with deionized water. After centrifugation and filtration, vacuum dry it at 80 °C for 12 h;
[0046] Step 4) Place the washed and dried powder in a crucible and put it into a tube furnace. Pass a mixed gas of 20% hydrogen and argon, heat it up to 400 °C at a rate of 10 °C / min, and hold for 2 h for annealing reduction to obtain a copper / nickel-graphite composite powder;
[0047] Step 5) Put the composite powder into a rapid sintering furnace and carry out hot pressing sintering at 900 °C, 50 MPa, and argon atmosphere to obtain a composite block.
[0048] Step 6) The thickness of the prepared composite block is less than 1 mm. Use a four-point probe conductivity measurement device to measure the conductivity at room temperature. This device consists of a nanovoltmeter and a constant current source. The specific measurement method is the same as that in Step 6 of Example 1. Finally, the conductivity of the copper-nickel alloy-graphite interlayer composite material block is calculated to be 58.8×10 6 S / m, 101.3% IACS, exceeding the international annealed copper standard. This shows that the copper-nickel alloy-graphite interlayer composite material block prepared in this example meets the usage requirements. Example 5
[0049] This example includes the following steps:
[0050] Step 1) Dry 1 g of high-purity flake graphite, 2.5 g of anhydrous copper chloride, and 0.1 g of anhydrous nickel chloride (2.8 wt%) powder at 120 °C for 2 h. After mixing evenly, place them in a quartz tube, evacuate to 10 Pa and seal;
[0051] Step 2) Place the sealed quartz tube in an electric heating furnace, heat it up to 520 °C at a rate of 10 °C / min, and carry out a composite intercalation reaction for 7 days;
[0052] Step 3) Wash the prepared composite chloride-graphite intercalation compound powder with deionized water. After centrifugation and filtration, vacuum dry it at 80 °C for 12 h;
[0053] Step 4) Place the washed and dried powder in a crucible and put it into a tube furnace. Pass a mixed gas of 20% hydrogen and argon, heat it up to 400 °C at a rate of 10 °C / min, and hold for 2 h for annealing reduction to obtain a copper / nickel-graphite composite powder;
[0054] Step 5) Put the composite powder into a rapid sintering furnace and carry out hot pressing sintering at 900 °C, 50 MPa, and argon atmosphere to obtain a composite block.
[0055] Step 6) The thickness of the prepared composite block is less than 1 mm, and the conductivity is measured at room temperature using a four-point probe conductivity measurement device. This device consists of a nanovoltmeter and a constant current source. The specific measurement method is the same as that in Step 6 of Example 1. Finally, the conductivity of the copper-nickel alloy-graphite interlayer composite block is calculated to be 59.3×10 6 S / m, 102.3% IACS, exceeding the international annealed copper standard. This shows that the copper-nickel alloy-graphite interlayer composite block prepared in this example meets the usage requirements. Example 6
[0056] This example includes the following steps:
[0057] Step 1) 1 g of nano-graphite powder, 2.5 g of anhydrous copper chloride, and 0.1 g of anhydrous nickel chloride (2.8 wt%) powder are dried at 120 °C for 2 h. After mixing evenly, they are placed in a quartz tube, evacuated to 10 Pa, and sealed.
[0058] Step 2) The sealed quartz tube is placed in an electric heating furnace and heated to 520 °C at a rate of 10 °C / min for a composite intercalation reaction for 7 days.
[0059] Step 3) The prepared composite chloride-graphite intercalation compound powder is washed with deionized water, centrifuged, filtered, and then vacuum dried at 80 °C for 12 h.
[0060] Step 4) The washed and dried powder is placed in a crucible and put into a tube furnace. A mixed gas of 20% hydrogen and argon is introduced, and the temperature is raised to 400 °C at a rate of 10 °C / min and held for 2 h for annealing reduction to obtain copper / nickel-graphite composite powder.
[0061] Step 5) The composite powder is put into a rapid sintering furnace and hot press sintered at 900 °C, 50 MPa, and in an argon atmosphere to obtain a composite block.
[0062] Step 6) The thickness of the prepared composite block is less than 1 mm, and the conductivity is measured at room temperature using a four-point probe conductivity measurement device. This device consists of a nanovoltmeter and a constant current source. The specific measurement method is the same as that in Step 6 of Example 1. Finally, the conductivity of the copper-nickel alloy-graphite interlayer composite block is calculated to be 60.1×10 6 S / m, 103.6% IACS, exceeding the international annealed copper standard. This shows that the copper-nickel alloy-graphite interlayer composite block prepared in this example meets the usage requirements. Comparative Example 1
[0063] This comparative example includes the following steps:
[0064] Step 1) Dry 1 g of expanded graphite and 2.5 g of anhydrous copper chloride powder at 120 °C for 2 h. After mixing evenly, place them in a quartz tube, evacuate to 10 Pa and seal.
[0065] Step 2) Place the sealed quartz tube in an electric heating furnace, heat it up to 520 °C at a rate of 10 °C / min, and carry out a composite intercalation reaction for 7 days.
[0066] Step 3) Wash the prepared composite chloride-graphite intercalation compound powder with deionized water. After centrifugation and filtration, dry it in vacuum at 80 °C for 12 h.
[0067] Step 4) Place the washed and dried powder in a crucible and put it into a tube furnace. Pass a mixed gas of 20% hydrogen and argon, heat it up to 400 °C at a rate of 10 °C / min, and keep it at this temperature for 2 h for annealing reduction to obtain a copper / nickel-graphite composite powder.
[0068] Step 5) Put the composite powder into a rapid sintering furnace and carry out hot pressing sintering at 900 °C, 50 MPa, and in an argon atmosphere to obtain a composite block.
[0069] Step 6) The thickness of the prepared composite block is less than 1 mm. Use a four-point probe method conductivity measurement device to test the conductivity at room temperature. This device consists of a nanovoltmeter and a constant current source. The specific test method is the same as that in Step 6 of Example 1. Finally, the conductivity of the copper-nickel alloy-graphite interlayer composite material block is 52.6×10 6 S / m, 90.8% IACS, close to the international annealed copper standard. This shows that the copper-nickel alloy-graphite interlayer composite material block prepared in this example meets the usage requirements.
[0070] Through specific actual experiments, a copper-nickel alloy-graphite interlayer composite material was prepared under the setting of a mass ratio of graphite:CuCl2:NiCl = 1:2.5:0.1 and a composite intercalation reaction temperature of 520 °C. The conductivity was tested at room temperature using a four-point probe method conductivity measurement device. This device consists of a constant current source and a nanovoltmeter. Four probes are placed around the sample. For the first measurement, current is passed through the first and second probes, and the voltage is measured between the third and fourth probes; for the second measurement, current is passed through the second and third probes, and the voltage is measured between the fourth and first probes. Finally, the obtained conductivity reaches 106.1% IACS.
[0071] Compared with the prior art, the present invention realizes a breakthrough in the ultra-high conductivity performance of the copper-nickel alloy-graphite interlayer composite material by introducing a copper / nickel composite chloride intercalating agent for composite intercalation reaction. The prepared copper-nickel alloy-graphite interlayer composite material still maintains a relatively regular layered structure. The interface quality in the graphene-copper matrix composite material is effectively improved by interfacial modification with trace heteroelements, and at the same time, the damage to the conductivity caused by electron scattering is avoided.
[0072] The above specific embodiments can be locally adjusted in different ways by those skilled in the art without departing from the principles and purposes of the present invention. The protection scope of the present invention is subject to the claims and is not limited by the above specific embodiments. All implementation solutions within its scope are subject to the present invention.
Claims
1. A preparation method of a high-conductivity copper-nickel alloy-graphite intercalation composite material, characterized in that, The dried graphite powder is mixed uniformly with a mixture of copper chloride and nickel chloride as an intercalating agent, and after vacuum sealing treatment, it is heated to carry out a composite intercalation reaction to prepare a composite chloride-graphite intercalation compound. After further annealing and reduction in a hydrogen-argon mixed gas atmosphere to obtain a copper / nickel-graphite composite powder, a copper-nickel alloy-graphite interlayer composite material for preparing a conductor with a conductivity reaching 106.1% IACS is obtained by hot pressing and sintering.
2. The preparation method of the highly conductive copper-nickel alloy-graphite intercalation composite material according to claim 1, characterized in that, The drying treatment is to heat at 100 - 120 °C for 1 - 2 h to remove water vapor in the powder.
3. The preparation method of the highly conductive copper-nickel alloy-graphite intercalation composite material according to claim 1, characterized in that, The graphite powder can be selected from one or more of expanded graphite, high-purity flake graphite, and nano-graphite powder.
4. The preparation method of the high-conductivity copper-nickel alloy-graphite intercalation composite material according to claim 1, characterized in that, The components of the intercalating agent satisfy a mass ratio of C:CuCl₂:NiCl = 1:(1.5 - 2.5):(0.05 - 0.1).
5. The preparation method of the highly conductive copper-nickel alloy-graphite intercalation composite material according to claim 1, characterized in that, The vacuum sealing treatment means: putting a quartz tube with a diameter of 5 - 6 mm filled with the mixed powder into an argon environment, evacuating to 10 Pa and sealing.
6. The preparation method of the highly conductive copper-nickel alloy-graphite intercalation composite material according to claim 1, characterized in that, The composite intercalation reaction is carried out at 450 - 550 °C for 5 - 7 days.
7. The preparation method of the high-conductivity copper-nickel alloy-graphite intercalation composite material according to claim 1, characterized in that, Before annealing and reduction, the composite chloride-graphite intercalation compound is first washed and dried. Specifically: it is washed with deionized water to remove residual chlorides, centrifuged at 3000 - 5000 r / min for 3 - 10 min, filtered, and then vacuum dried at 70 - 80 °C for 12 - 24 h.
8. The preparation method of the highly conductive copper-nickel alloy-graphite intercalation composite material according to claim 1 or 7, characterized in that, The annealing and reduction means: putting the washed and dried composite intercalation compound powder into a crucible and placing it in a tube furnace, introducing a mixed gas of 20% hydrogen and argon, with a temperature of 400 - 500 °C, keeping warm for 1 - 2 h, and then quickly cooling the tube furnace to room temperature to obtain a copper / nickel-graphite composite powder.
9. The preparation method of the highly conductive copper-nickel alloy-graphite intercalation composite material according to claim 1, characterized in that The hot pressing and sintering means: under argon protection in a rapid sintering furnace, hot pressing and sintering are carried out using a graphite mold with a diameter of 30 - 40 mm, the sintering temperature is 700 - 1000 °C, the pressure is 10 - 200 MPa, and the holding time is 10 - 30 min.
10. A composite chloride-graphite intercalation compound prepared by the method according to any one of claims 1-9, characterized in that, Specifically, copper / nickel composite chloride is inserted into the graphite layer through the composite intercalation reaction, and chloride ions are removed after reduction to obtain a copper / nickel-graphite composite powder; the internal structure of the bulk material obtained by hot pressing and sintering is a layered configuration with a small amount of Ni-modified copper / nickel-graphite combination at the interface.